Immune-Mediated Damage Completes the Parabola: Cryptococcus neoformans Pathogenesis Can Reflect the Outcome of a Weak or Strong Immune Response - Liise-anne Pirofski (American Society for Microbiology, 2017)
ABSTRACT Cryptococcosis occurs most frequently in immunocompromised individuals. This has led to the prevailing view that this disease is the result of weak immune responses that cannot control the fungus. However, increasingly, clinical and experimental studies have revealed that the host immune response can contribute to cryptococcal pathogenesis, including the recent study of L. M. Neal et al. (mBio 8:e01415-17, 2017, https://doi.org/10.1128/mBio.01415-17 ) that reports that CD4+ T cells mediate tissue damage in experimental murine cryptococcosis. This finding has fundamental implications for our understanding of the pathogenesis of cryptococcal disease; it helps explain why immunotherapy has been largely unsuccessful in treatment and provides insight into the paradoxical observation that HIV-associated cryptococcosis may have a better prognosis than cryptococcosis in those with no known immune impairment. The demonstration that host-mediated damage can drive cryptococcal disease provides proof of concept that the parabola put forth in the damage-response framework has the flexibility to depict complex and changing outcomes of host-microbe interaction.